Investigation of Lockout / Tagout Procedure Failure in Machine Maintenance Process - Luciana Triani Dewi (Jurnal Teknik Industri, 2018)
Lockout/tag out (LOTO) refers to specific practices and procedures to stop the release of hazardous energy and turnoff machinery and equipment during service or maintenance activities. An effective LOTO system will ensure the workers are protected from the unexpected conditions during maintenance activities. This paper focus on incidents of LOTO system failures in an electricity power industry. LOTO system had implemented for many years in the company, but many incidents of LOTO system failure was still happened. The purpose of the research was to investigate the cases of incident caused by LOTO procedure failures. The research was conducted using descriptive analytical approach to analyse the cases of incident to find the root causes and develop the solution. Main data used in the research was document of incidents and was analysed by Systematic Cause Analysis Technique (SCAT). The result of investigation showed the root causes of LOTO system failure were caused by individual, job and management factors. Based on SCAT chart synthesis, the control actions were identified. The identified control movement were improve operational procedure of LOTO and proposed job description of supervisor. Evaluation of control action concluded that basically the suggestions were feasible to implement and some adjustments were needed due to implementation.